2004
DOI: 10.1007/s00595-003-2680-6
|View full text |Cite
|
Sign up to set email alerts
|

Resection of a Solitary Pancreatic Metastasis from Renal Cell Carcinoma with a Gallbladder Carcinoma: Report of a Case

Abstract: Most metastatic pancreatic tumors are detected at an advanced stage and are not considered suitable for surgery; however, resection is sometimes indicated for a solitary pancreatic metastasis from renal cell carcinoma (RCC) and improves the prognosis. We report such a case, in which the hilar liver was resected with lymph node dissection and distal pancreatectomy. Histological examination revealed regional lymph node metastasis of gallbladder carcinoma (GBC), but all the surgical margins were free of cancer. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Immunohistochemically, primary clear cell carcinoma of the GB is strongly positive for CEA and CK7, and moderately positive for CK10, but negative for vimentin. On the other hand, metastatic RCC of the GB is positive for vimentin, but negative for CEA, CK7, and CK10 ,. Because our immunohistochemical findings were nearly consistent with the reported findings, we finally diagnosed metastatic GB tumor from RCC rather than primary clear cell carcinoma of the GB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Immunohistochemically, primary clear cell carcinoma of the GB is strongly positive for CEA and CK7, and moderately positive for CK10, but negative for vimentin. On the other hand, metastatic RCC of the GB is positive for vimentin, but negative for CEA, CK7, and CK10 ,. Because our immunohistochemical findings were nearly consistent with the reported findings, we finally diagnosed metastatic GB tumor from RCC rather than primary clear cell carcinoma of the GB.…”
Section: Discussionmentioning
confidence: 98%
“…In our review of the English‐language literature, we found 12 reported cases of GB metastasis of RCC (summarized in Table 1). The presumed mode of GB involvement from intraperitoneal organs is usually direct invasion or peritoneal implantation, while metastases from extraperitoneal organs, such as the lung, kidney, breast, and malignant melanoma, follow a hematogenous route ,. Hematogeneous metastases to GB initially occur as small flat nodules below the mucosal layer and then they grow as a pedunculated nodule and resemble a primary GB carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the majority of patients were asymptomatic. Some have suggested that although isolated presentations of primary RCC and primary gallbladder can occur in the same patient, the preoperative diagnosis of gallbladder metastasis should be considered in patients with a history of RCC [8,9]. As of today, specific postoperative screening for gallbladder metastasis in asymptomatic patients with a history of RCC would be inadvisable, since the number needed to screen to identify a single gallbladder metastasis would be in the thousands; however, when cross-sectional imaging is performed pre- or post-operatively, a “closer look” at the gallbladder is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent sites of metastasis include the lung parenchyma (50% to 60%), [2] bone (30% to 40%), [3] liver (30% to 40%), and brain (5%) [4]. Other rare sites of metastasis include pancreas [5,6], adrenal gland [7,8], parotid gland [9], maxilla, pharynx etc. Even with early-stage disease, late metastases can occur after complete resection.…”
Section: Introductionmentioning
confidence: 99%